Redescription of Ilyocryptus raridentatus Smirnov, 1989 (Cladocera: Ilyocryptidae) - Dadykin, Ivan A.; Ðịnh, Cù Nguyên; Shiel, Russell J.; Kotov, Alexey A. (Zootaxa, 2024)
During recent years, many taxa of water fleas (Crustacea: Cladocera) with wide distribution ranges were revised and finally accepted as groups of cryptic species. Here we provide a redescription of Ilyocryptus raridentatus Smirnov, 1989 (Anomopoda: Ilyocryptidae). Our study clearly confirms that I. raridentatus belongs to the sarsi-group based on incomplete moulting, absence of dorsal keel, structure of antennule, thoracic limb I and postabdomen. The species is widely distributed in Australia and East Asia (Malaysia, Thailand, Vietnam, Central China, Japan, South Korea) and penetrates north to the Far East of Russia. A morphological variability among different populations of I. raridentatus does not exceed an intrapopulational level. I. raridentatus seems to be a relatively rare species with a benthic lifestyle similar to its congeners.